Influence of Foreign Words on Our Native Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The influence of foreign terms on Uzbek language was examined in this article. This leads to an examination of the issues that emerge and a statement of the beneficial aspects. This scholarly paper examines a number of terms that were borrowed from English and Russian into Uzbek. For instance, the origins, range of current usage, and shared characteristics of certain English and Russian neologisms in the Uzbek language are disclosed in this article. The data was gathered from many dictionaries including the "Annotated Dictionary of the Uzbek Language".